Compulsary jurisdiction of the international court of justice - "Anand, R.P." (Gurgaon, 2008)
This is a very useful study of what must be regarded as one of the central problems in international law...The comprehensive treatment of the whole problem is, however, a useful addition to the existing literature.
Keywords: Jurisdiction